2015
DOI: 10.1002/ptr.5533
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Lycopene Against PTZ-induced Kindling Seizures in Mice: Possible Behavioural, Biochemical and Mitochondrial Dysfunction

Abstract: Oxidative stress and mitochondrial dysfunction are the major contributing factors in the pathophysiology of various neurological disorders. Recently, antioxidant therapies aimed at reducing oxidative stress gained a considerable attention in epilepsy treatment. Lycopene, a carotenoid antioxidant, has received scientific interest in recent years. So, the present study has been designed to evaluate the neuroprotective effect of lycopene against the pentylenetetrazol (PTZ)-induced kindling epilepsy. Laca mice rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It also attenuated Ab-induced mitochondrial damage in isolated cortical neurons (Qu et al, 2011;Qu et al, 2016) and reduced proinflammatory cytokines in the brain of Ab-exposed animals (Liu et al, 2018). Similar effects of lycopene on oxidative and mitochondrial damage have been demonstrated in a pentylenetetrazol-induced model of seizure where it also decreased convulsive activity (Bhardwaj and Kumar, 2016;Kumar et al, 2016). Lycopene also decreased markers of oxidative stress and reduced neuronal cell loss in models of PD and stroke (Prema et al, 2015;Lei et al, 2016) and was able to attenuate BBB disruption and neurological deficits in a model of subarachnoid hemorrhage (Wu et al, 2015).…”
Section: Botanically Derived Nrf2 Activatorsmentioning
confidence: 64%
“…It also attenuated Ab-induced mitochondrial damage in isolated cortical neurons (Qu et al, 2011;Qu et al, 2016) and reduced proinflammatory cytokines in the brain of Ab-exposed animals (Liu et al, 2018). Similar effects of lycopene on oxidative and mitochondrial damage have been demonstrated in a pentylenetetrazol-induced model of seizure where it also decreased convulsive activity (Bhardwaj and Kumar, 2016;Kumar et al, 2016). Lycopene also decreased markers of oxidative stress and reduced neuronal cell loss in models of PD and stroke (Prema et al, 2015;Lei et al, 2016) and was able to attenuate BBB disruption and neurological deficits in a model of subarachnoid hemorrhage (Wu et al, 2015).…”
Section: Botanically Derived Nrf2 Activatorsmentioning
confidence: 64%
“…Decreased low-density lipoprotein-cholesterol (LDL), total cholesterol (TC), and thiobarbituric acid-reacting substances [58] Lowered very-low-density lipoprotein-cholesterol (VLDL), triglycerides (TG) and increased high-density lipoprotein-cholesterol (HDL) level [59] Decreased inflammatory factors (CRP, interleukin (IL)-6), pulse wave velocity, adhesion molecules and endothelial function [60] Lowered Improved mitochondrial enzymatic activities, kindling score, oxidative stress [74] Decreased impairment in biochemical, behavioral, neuroinflammatory and neurochemical markers [75] Boneprotective Osteoblasts differentiation improved [76] Modified the biomarkers of serum osteocalcin, bone metabolism, crosslinked carboxyterminal telopeptides and N-terminal propeptide of type 1 collagen in serum Downregulated the osteoclast differentiation concurrent Up-regulated the osteoblasts alongside GPx, SOD, and CAT activities [77] Targeting reproductive disorders…”
Section: Cardioprotectivementioning
confidence: 99%
“…Rats were assessed for various behavioral and biochemical parameters (SOD, lipid peroxidation, CAT, decreased GSH and nitrite) and activities of the enzymes of mitochondria (I, II, and IV) in the brain. Based on the findings, lycopene (5, 10 mg/kg) considerably improved mitochondrial enzymatic activities, kindling score, and oxidative stress as compared to control [74]. The neuroprotective role of lycopene was also studied in a male C57BL/6 mice model of bilateral common carotid artery occlusion (BCCAO).…”
Section: Neuroprotectivementioning
confidence: 99%
“…In addition to these health benefits, lycopene is also thought to have brain protection. This concept stems from the observation that lycopene can penetrate the blood-brain barrier (Khachik et al 2002), ameliorate pentylenetetrazol-induced seizures (Bhardwaj and Kumar 2016;Kumar et al 2016), as well as attenuate ischemia-or neurotoxins-induced brain injury and memory impairment in experimental animals (Fujita et al 2013;Lei et al 2016;Prakash and Kumar 2013;Sachdeva and Chopra 2015). Furthermore, it was reported that dietary intake of lycopene can reduce the risks D r a f t of neurodegenerative disorders, especially Alzheimer's disease (Bun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported that dietary intake of lycopene can reduce the risks D r a f t of neurodegenerative disorders, especially Alzheimer's disease (Bun et al 2015). Although the underlying mechanism through which lycopene exerts its neuroprotective effect has not been clearly elucidated, inhibited inflammatory processes, antioxidant activity, oxygen-free radicals scavenging, and improved mitochondrial dysfunction have been implicated (Bhardwaj and Kumar 2016;Fujita et al 2013;Sachdeva and Chopra 2015).…”
Section: Introductionmentioning
confidence: 99%